The Effect Of E-Trust on Acceptance of Customer Service Digital Machine: An Approach to The Technology Acceptance Model - Santi Adiraharjo, Klara (Universitas Tidar, 2024)
This study aims to analyze the effect of e-trust on acceptance of digital customer service machine with the Technology Acceptability Modeefl (TAM) approach. The study used purposive sampling with a valid sample of 306 respondents. The respondents were selected on the basis of a specific criterion, namely a customer who has transacted with CS Digital banking at least once in the last 3 months. Partial Least Square (SmartPLS 3.3.4) was chosen as an analysis method to evaluate the results of the study. The results of the first hypothesis test show that perceived ease of use is proven to have no significant influence on perceived usefulness but has an influence on attitude and intention to use. While perceived usefulness influences attitude, it does not have a significant influence on intention to use. Furthermore, attitude is proven to have a direct influence on intention to use. Then, e-trust has an influence on perceived usefulness, perceived ease of use, attitude, and intention to use. Finally, intention to use succeeded in having an influence on actual system use.